The gut microbiota and its role in the development of allergic disease: a wider perspective. Issue 1 (January 2015) - West, C. E.; Jenmalm, M. C.; Prescott, S. L.
Summary The gut microbiota are critical in the homoeostasis of multiple interconnected host metabolic and immune networks. If early microbial colonization is delayed, the gut‐associated lymphoid tissues (GALT) fail to develop, leading to persistent immune dysregulation in mice. Microbial colonization has also been proposed as a major driver for the normal age‐related maturation of both Th1 and T regulatory (Treg) pathways that appear important in suppressing early propensity for Th2 allergic responses. There is emerging evidence that resident symbionts induce tolerogenic gut‐associated Treg cells and dendritic cells that ensure the preferential growth of symbionts; keeping pathogenic strains in check and constraining proinflammatory Th1, Th2, and Th17 clones. Some effects of symbionts are mediated by short‐chain fatty acids, which play a critical role in mucosal integrity and local and systemic metabolic function and stimulate the regulatory immune responses. The homoeostatic IL‐10/TGF‐β dominated tolerogenic response within the GALT also signals the production of secretory IgA, which have a regulating role in mucosal integrity. Contrary to the 'sterile womb' paradigm, recent studies suggest that maternal microbial transfer to the offspring begins during pregnancy, providing a pioneer microbiome. It is likely that appropriate microbial stimulation both pre‐ and postnatally is required for optimal Th1 and Treg development to avoid the pathophysiological processes leading to allergy. Disturbed gut colonization patterns have been associated with allergic disease, but whether microbial variation is the cause or effect of these diseases is still under investigation. We are far from understanding what constitutes a 'healthy gut microbiome' that promotes tolerance. This remains a major limitation and might explain some of the inconsistency in human intervention studies with prebiotics and probiotics. Multidisciplinary integrative approaches with researchers working in networks, using harmonized outcomes and methodologies, are needed to advance our understanding in this field.